Diagnosis and management of cardiovascular risk in rheumatoid arthritis: main challenges and research agenda. (4th March 2023) - Atzeni, Fabiola; Maiani, Silvia; Corda, Marco; Rodríguez-Carrio, Javier
ABSTRACT: Introduction: Rheumatoid arthritis (RA) exhibit a cardiovascular (CV) risk that is 1.5–2.0 times higher compared to the general population. This CV risk excess is likely caused by the involvement of chronic inflammation and immune dysregulation. Therefore, conventional algorithms and imaging techniques fail to fully account for this risk excess and provide a suboptimal risk stratification, hence limiting clinical management in this setting. Areas covered: Compelling evidence has suggested a role for adaptations of conventional algorithms (Framingham, SCORE, AHA, etc) or the development of RA-specific algorithms, as well as the use of a number of several, noninvasive imaging techniques to improve CV risk assessment in RA populations. Similarly, in-depth analyses of atherosclerosis pathogenesis in RA patients have shed new light into a plethora of soluble biomarkers (such as inflammatory cytokines, vascular remodeling mediators or autoantibodies) that may provide incremental value for CV risk stratification. Expert opinion: Extensive research has demonstrated a lack of performance of chart adaptations in capturing real CV risk in RA population, as well as for RA-specific algorithms. Similarly, limitations have been detected in the use of soluble mediators. The development of a novel, RA-specific algorithm including classical and non-traditional risk factors may be advisable.